DETERMINASI VOLATILITAS KURS RUPIAH TERHADAP DOLAR AMERIKA - Ade Irma Nurhasanah; Soeharjoto Soekapdjo (Politeknik Negeri Batam, 2019)
Purpose of this study is to know about Rupiah exchange rate to US Dollar determination with quarterly time series data, from 2010-2017. Using Error Connection Model (ECM) with regression method, and dependent variable is Rupiah exchange rate to US Dollar, and independent variable is foreign debt, current account balance, and Sertifikat Bank Indonesia (SBI) interest rate. Result shown that at short term, foreign debt and current account were not significant, but SBI interest rate have a positive and significant effect from Rupiah to US Dollar. For long term, all of independent variable have positive and significant to dependent variable.